Incarnation in Incarnation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Iranyan Vadai Padalam is sung as one of the gems of the Navaratna garland of Kambaramayana.  This article discusses the reason for the inclusion of this chapter ‘Iranyan Vadai Padalam’.  It also speaks about incarnation of God, whose motive is to establish Dharma and destroy Adharma.  This chapter highlights the bhakthi of Prakalathan, son of Iranya and describes the arrogant king Iranya’s death.  The poet Kambar insists the people to give up their ego which may lead to destruction.  He  wants to announce the end of Ramayana beforehand and also explained the main mantra (Om Namo Narayana) of Sri Vasihnavism.